(untitled) (Journal of the College of Basic Education, 2022)
able to play their role in communicating knowledge to students and developing their thinking, due to rapid cognitive development as a result of tremendous technological progress in all walks of life, and this progress and development required attention to the development of students’ mentality and providing them with mental skills to be able to keep pace with the development that occurred In the world. As a result of the foregoing, the current research problem was formed through an exploratory study conducted by the researcher to identify the extent to which primary school students benefited from the art education subject and what are the capabilities of their mastery of the skills of this material and employ it in accomplishing artistic works. The possibilities of applying general performance skills, And the existence of a weakness in the process of applying the elements and foundations of artistic work in the art education subject, and it is felt that there is a problem that needs to be addressed through searching for modern teaching methods, as I found that teaching according to the modeling method may achieve the goal that you seek. Therefore, the aim of the current research is to identify (the effectiveness of teaching by modeling method in mastering planning skills and colors for primary school pupils in art education), and for the purpose of validating this goal the researcher has put (6) zero hypotheses. The research community consisted of fifth-grade primary students, in Baghdad Governorate / General Directorate for Education of Karkh / First. An intentional sample of them (50) male and female students from the (Martyr Kamel Shabib Primary School) was selected. (The researcher) designed the fee analysis form, as this form consisted of (18) primary fields from which (59) secondary fields are branched, and it was presented to a group of experts and specialists in art education, plastic arts, psychology, education technology, measurement and evaluation, and after Amendment to it through addition and deletion, the form has become in its final form consisting of (24) main fields branching out of (41) secondary fields, and thus the tool gained apparent validity, after that the stability was verified by analyzing the researcher with itself after a period of two weeks and the use of external analysts and the rate was The year of th S (86%), with the total fees that were analyzed amounted to (50) fee. In order to reach the results of the research, the researcher used the following statistical methods: - T-Test equation, Cooper equation, Pearson correlation equation. The results discussed and the researcher concluded that the process of modeling the skill and displaying it in front of the student sequentially leads to clarity Information and increase the ability to acquire skills and knowledge and raise their level of education. She recommended preparing teachers to prepare them to be able to use effective methods of teaching, and suggested conducting similar studies for the current study in another subject of art education and for other academic stages.